Recent Advances in the Synthesis of Bowl-Shaped Aromatic Compounds - Stępień, Marcin (Synlett, 2013)
This review provides a brief account of the methodology used for the synthesis of bowl-shaped aromatic compounds, illustrated by recent literature examples. Special attention is given to the latest developments such as surface-catalyzed cyclodehydrogenations, alumina-mediated ring closures, and the fold-in approach.
Keywords: arenes; cyclophanes; fused-ring systems; heterocycles; macrocycles